Entrepreneurial universities and the development model for public universities in Vietnam - Đinh, Văn Toàn (Allied Business Academies, 2020)
This article summarizes and clarifies the theoretical and practical characteristics and elements of entrepreneurial universities. Based on the results of a survey administered to universities and in-depth interviews with administrators and lecturers in management roles at four public universities in North of Vietnam, it proposes an organizational model for developing entrepreneurial universities in the context of public universities in Vietnam and discusses related policy implications.